Activation of prolyl hydroxylase‐2 for stabilization of mitochondrial stress along with simultaneous downregulation of HIF‐1α/FASN in ER + breast cancer subtype. (5th April 2019) - Devi, Uma; Singh, Manjari; Roy, Subhadeep; Gupta, Pushpraj S.; Ansari, Mohd. Nazam; Saeedan, Abdulaziz S.; Kaithwas, Gaurav
Abstract : The present study was undertaken to inquest the chemical activation of prolyl hydroxylase‐2 for the curtailment of hypoxia‐inducible factor‐1α and fatty acid synthase. It was well documented that hypoxia‐inducible factor‐1α and fatty acid synthase were overexpressed in mammary gland carcinomas. After screening a battery of compounds, BBAP‐2 was retrieved as a potential prolyl hydroxylase‐2 activator and validates its activity using ER + MCF‐7 cell line and n‐methyl‐n‐nitrosourea‐induced rat in vivo model, respectively. BBAP‐2 was palpable for the morphological characteristics of apoptosis along with changes in the mitochondrial intergrity as visualized by acridine orange/ethidium bromide and JC‐1 staining against ER + MCF‐7 cells. BBAP‐2 also arrest the cell cycle of ER + MCF‐7 cells at G2/M phase. Afterward, BBAP‐2 has scrutinized against n‐methyl‐n‐nitrosourea‐induced mammary gland carcinoma in albino Wistar rats. BBAP‐2 restored the morphological architecture when screened through carmine staining, haematoxylin and eosin staining, and scanning electron microscopy. BBAP‐2 also delineated the markers of oxidative stress favourably. The immunoblotting and mRNA expression analysis validated that BBAP‐2 has a potentialty activate the prolyl hydroxylase‐2 with sequential downregulating effect on hypoxia‐inducible factor‐1α and its downstream checkpoint. BBAP‐2 also fostered apoptosis through mitochondrial‐mediated death pathway. The present study elaborates the chemical activation of prolyl hydroxylase‐2 by which the increased expression of HIF‐1α and FASN can be reduced in mammary gland carcinoma.